Obesity and adiposity of 3- to 6-year-old children born to mothers with hyperglycaemia first detected in pregnancy in an urban South African setting - Larske M. Soepnel; Veronique Nicolaou; Christine Slater; Glory Chidumwa; Naomi S. Levitt; Kerstin Klipstein-Grobusch; Shane A. Norris (Taylor & Francis Group, 2021)
Background Understanding the association between maternal metabolic conditions in pregnancy and the risk of childhood overweight, a growing concern in sub-Saharan Africa (SSA), helps to identify opportunities for childhood obesity prevention. Aim To assess the association between hyperglycaemia first detected in pregnancy (HFDP) (gestational diabetes mellitus [GDM] and diabetes in pregnancy [DIP]) and child obesity and adiposity in pre-school-aged children in South Africa, independently of maternal BMI. Subjects and methods Measurement of anthropometry and fat mass index (FMI) by the deuterium dilution method was done for 102 3-6-year-old children born to mothers with HFDP and 102 HFDP-unexposed children. Hierarchical regression analysis and generalised structural equation modelling (GSEM) were performed. Results The prevalence of overweight/obesity was 10.5% and 11.1% in children exposed to GDM and DIP, respectively, and 3.9% in the HFDP-unexposed group. Log-transformed FMI was significantly higher in the DIP-exposed group (β = 0.166, 95% CI = 0.014-0.217 p= .026), but not when adjusting for maternal pregnancy BMI (β = 0.226, 95% CI = 0.003-0.015, p = .004). GSEM showed significant total effects of maternal BMI and birth weight on FMI/BMI. Conclusions Maternal pregnancy BMI seems to play a greater role in the development of childhood adiposity than maternal hyperglycaemia, requiring further research and identifying maternal BMI as a relevant prevention target in our setting.